How Greece Developed its Agriculture, 1947-67 - Myrick, D. C.; Witucki, Lawrence A.; Myrick, D. C. (Washington : Economic Research Service, U.S. Dept. of Agriculture; for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1971)
From 1947 to 1967, the agricultural output of Greece grew at a compound annual rate of 4.9 percent, meeting the needs of increased population and rising levels of living, accomplishing import substitution, and increasing exports. With little opportunity to expand agricultural land, Greece achieved most of the growth from intensification. The proportion of capital to all inputs increased from 19.5 to 38.3 percent, and the proportion of cropland irrigated, from 7 to almost 17 percent. Improved technology was developed and widely disseminated. A favorable economic environment was provided by price supports, bonuses, and subsidies, which -- together with investment support -- involved substantial capital and income transfers from the general economy. Massive external assistance through 1952, and at reduced levels until 1965, was a major factor in growth of the Greek economy. Population grew at only 0.8 percent, but the proportion of population in agriculture was high, about 50 percent. Labor productivity in agriculture was low, as reflected by the proportion of gross domestic product originating in the agricultural sector, yet the rest of the economy was not able to provide alternative economic opportunity.
Bibliography: p. 129-132.
lje 12/07/17
Loans
Keywords: Agriculture; Agricultural development-Greece